تحسين خواص أجهزة اللواقط الشمسية باستخدام مواد انتقائية خاصة - تقلا, جوني; غاتا, عدنان; حموي, نقولا (Latakia University Journal -Engineering Sciences Series, 2019)
إنَّ وظيفة الأسطح اللاقطة للطاقة الشمسية هي تحويل الإشعاع الشمسي الوارد إلى طاقة حرارية والحد من الضياعات الحرارية بتأثير الإشعاع الحراري. هذه الاحتياجات (تشمل تأمين أقصى قيم امتصاصية للإشعاع الشمسي – ضمن حدود الطول الموجي 0.29-2.5 ميكرومتر وأدنى انبعاث للأشعة التحت الحمراء الحرارية 2.5 ميكرومتر) يمكن تحقيقها من خلال استخدام طبقة مغلفة تتميّز بخواص أطيافية إنتقائية على السطح الماص (اللاقط) (عادةً مادة النحاس – الألمنيوم أو الفولاذ)، وتستطيع العوامل المناخية البالغة الدقة أن تترك آثاراً ضارة على السطح اللاقط وتضعفه وتؤدي لضعف الخواص الضوئية، واعتماداً على الأبحاث الواسعة التي تتم لاستقصاء تأثيرات العوامل الجوية البالغة الدقة في الأسطح اللاقطة الشمسية بات من الممكن أن تتحدد العوامل المسببة لضعف الخواص وتراجع خواص الأسطح اللاقطة للطاقة الشمسية. وهذه العوامل هي كما يلي: حدوث تآكل أو تحلل بفعل الحمولة الحرارية – الحمل الحراري – أي الأكسدة. حدوث تآكل أو تحلل بفعل ارتفاع قيم الرطوبة أو تكثف الماء على السطح اللاقط. حدوث تآكل أو تحلل بفعل تلوث الهواء مثل ثاني أوكسيد الكبريت (تآكل جوي). إنَّ مركبات فلوريد الكربون معروفة بأنها مستخدمة كمواد مزلقة أو كمواد كاثودية في بطاريات الليثيوم الأولية، في حين أنَّ الأول يستند على تأثيرات السطح الضعيفة, وكذلك على وجود مجموعات C-F الصادة للماء. والحالة الثانية ناتجة عن تأثيرات شوارد الليثيوم في المواد أثناء عملية تفريغ البطاريات, وكذلك من إلفة اختزال فلوريد الكربون والفلورين الذي يساعد على تحقيق قيم طاقة نوعية عالية. وتتميز هذه المواد بثباتية حرارية عالية (حتى درجة حرارة 600 مئوية) وكونها ذات خواص طاردة للماء, إضافة إلى تميزها بخواص ضوئية ممتازة (مسحوق أبيض). فقد وجدنا من خلال هذا البحث تحسن لمردود المجمع الشمسي عند استخدام هذه المواد كمواد انتقائية للسطح الماص. The function of the absorber of a solar collector is to transform the incident solar irradiation into heat and to suppress heat losses due to thermal radiation. These requirements maximum absorption of the solar irradiation (in the wave length range from 0.29 to 2.5 mm) and minimum emittance in the thermal infrared (> 2.5 mm) are met by applying a spectrally selective coating onto the absorber substrate material (usually copper, aluminum or steel). Manifold micro – climatic influences can degrade the absorber in a collector causing the optical properties to deteriorate. Extensive investigation of the micro-climate in flat – plate collectors makes it possible to determine the factors, which are relevant to the degradation of solar energy absorber surfaces. These are: A- Degradation due to thermal load (oxidation). B- Degradation due to high humidity or condensation of water on the absorber surface (hydratization and hydrolysis). C- Degradation due to air polluants such as sulfur dioxide (atmosphere corrosion). Graphite fluorides are known for their application as lubricants or as cathodic materials in primary lithium batteries. While the first one is based on both weak surface interactions and on the presence of C-F hydrophobic groups, the second one results not only from the intercalation facility of lithium ions into the materials during the batteries discharge process but also from the high affinity of the graphite fluoride reduction by lithium and the very low equivalent weight of the carbon and fluorine elements which allow high specific energy densities to be reached. They have high thermal stability (up to 600 °C), hydrophobic, and high optical quality (white powder). This research work revealed improvement of the solar collector efficiency when these selective materials are added to the absorbent surface.